EVALUASI MODUL KULIAH DALAM PROSES PERKULIAH DI STMIK NURDIN HAMZAH: Evaluation, Modules, variables, indicators - -, Riswan (LP2M Universitas Nurdin Hamzah, 2018)
This research was conducted to evaluate student lecture modules made by lecturers. It is hoped that with this module the general objectives and specific instructional objectives of the course will be achieved well. The preparation of the lecture module is done by the lecturers themselves. In general, the module material is adjusted to the weight of the course. This module is a guide for students in the lecture process for one semester. Lecturers explain the material in the form of power points sourced from the module. To determine the quality of the module, a study was conducted on one of the Information Systems Project Management (MPSI) modules which researchers fostered in the fifth semester of the information system study program. Module assessment data is obtained through questionnaire online form with seven variables and several indicators. The evaluation results of the MPSI module on content accuracy variables, with valid indicators that answered